Creativity and 'expanding noetics' in world Englishes. Issue 1 (March 2015) - Nelson, Cecil L.; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT The title of Professor Yamuna Kachru's paper, 'Culture, Style, and Discourse: Expanding Noetics of English' (1992a) immediately raises an intriguing aspect of the spread and functions of world Englishes. The code, with all its potential variations in forms, may well serve as a window into and a means of approaching the 'cultures, styles, and discourses' of groups and people who are outside our own first‐hand and comfortable experiences. Excerpts from some culturally relevant texts, including some cited by Kachru, may serve to explicate and further substantiate this approach.